Comparison of versatile vs. dedicated detector as a luminescence detection platform - Lee, Sunghou (International Journal of Engineering and Technology, 2019)
The measurement of light emission signals in various experiments is a routine task to evaluate numerous biological events quantitatively. To accomplish these tasks, two types of detectors have been employed both EnVision (EnVision® Multilabel Plate Reader, Xcite) and Victor (VICTOR™ Luminescence Counter, Light). EnVision is a multimode instrument with complicated detection chamber to measure UV-Vis absorbance, fluorescence intensity, time-resolved fluorescence, fluorescence polarization and luminescence. However, Victor is   a simple dedicated platform for the luminescence detection. To test the luminescence detector functionality, a functional assay system for the G-protein coupled receptor was utilized. The aequorin based functional assay system for the calcium sensing receptor with HEK293-aeq/hCaS cells presented higher signal-to-noise ratio with Victor than EnVision for both of the endogenous and targeted receptors because of decreased background values. The dynamic range and data variation associated with the signal measurements were similar in both of instruments. In conclusion, both types of instrument provided comparable results for the luminescence detection that can be applied in variety of light emission experiments. However, the dedicated luminescence detector, Victor Light, with a simple optical path and jet-direct injectors provided extremely low background which is a real benefit for the flash-type luminescence applications.
Keywords: Aequorin; Calcium mobilization; Detector platform; Drug screening; G protein coupled receptor; Luminescence detection